THE MODEL OF A NEW UKRAINIAN RURAL SCHOOL AS A GUIDING PRINCIPLE FOR THE FUTURE - Nesterenko, Inna (Scientific Journal of Polonia University, 2023)
A small rural school has several orders of magnitude and fewer possibilities for meeting educational goals. The remoteness of settlements from scientific centers, the worse level of provision of the educational and material base, and the level of professional training of teachers, which does not always meet the requirements of work, caused this. A small school is not only to give students a sum of knowledge on the basics of science but also to teach them to think creatively, avoiding templates. The time under martial law in which our children are growing up is difficult. In today’s whirlwind, adults can’t always withstand enormous stress, so we rarely think about how our children live now. For those, we meet occasionally and for whom we are accountable to their parents and society. Education in rural schools is a cornerstone for discussion, and not only in our country. The debate continues, but in most cases, the arguments are not in favor of supporting small rural schools with small classes when there is an alternative at a reasonable distance. Rural schools in Ukraine, despite their high cost, cannot provide quality and affordable education services. The availability of premises and a few students in a class are all advantages of rural education. Success in rural areas significantly lags indicators of success in the city. And the results of the External Independent Evaluation (ZNO), both at the national level and in individual regions, confirm this every year. According to international experience and research, the most acceptable method of reform is school network optimization and the preservation of small schools only in remote, physically isolated communities, where it is simply impossible to transport students and teachers to school in an acceptable period. Optimization makes it possible to use funds and improves the quality of education in rural areas.